(untitled) (Education in the 21st Century, 2025)
The article examines traditional and modern methods of folklore documentation and their teaching and application at the Faculty of Armenian Philology of Yerevan State University. The latter is presented through conclusions drawn from personal experience. Unlike other branches of literature, the subject of folklore is not limited to the acquisition of book-based material alone, but also requires familiarity with living folklore in everyday practice and knowledge of the principles of its documentation. For a student studying this subject, it is important to be in the field, to listen, to observe, and to be able to record folklore materials. Through this process, the student more clearly understands the path taken by folklore texts—from the moment of their recording to their publication. In addition, by documenting folklore materials, the student contributes, to the extent possible, to the preservation of folklore. By studying the experience of different countries, the article presents modern methods of folklore documentation and archiving. It addresses contemporary technical tools used in fieldwork and their application, highlights the subtleties and ethical norms of conducting interviews with narrators, emphasizes the importance of questionnaires and the principles of their design, and discusses the specifics of documenting and recording materials. It also touches upon the principles of accurately preserving the narrator’s speech during transcription and processing of audio recordings, as well as modern means of archiving and creating repositories. The article emphasizes the necessity of teaching folklore fieldwork to philology students. It recommends that greater attention be devoted to the teaching and practical application of fieldwork at the Faculty of Armenian Philology. The author presents practical experiences already implemented within the course Folklore of the Armenian People for first-year students and through the “Folklore Fieldwork Club,” established at the faculty in 2021. It also includes the fieldwork program Recording, Mapping, and Archiving Artsakh Legends, carried out in 2024–2025 with YSU’s internal grant, during which students of the Faculty of Armenian Philology, under the author’s supervision, recorded a large number of Artsakh legends from locals who were forcibly displaced from Artsakh in 2023 and resettled in various regions of Armenia.